2010
DOI: 10.1002/ajim.20836
|View full text |Cite
|
Sign up to set email alerts
|

Working to eat: Vulnerability, food insecurity, and obesity among migrant and seasonal farmworker families

Abstract: Food insecurity is rooted in the cultural lifestyle of farmwork, poverty, and dependency. MSFW obesity and food insecurity require further study to determine the relationship with migration and working conditions. Networking and social support are important for MSFW families to improve food security. Policies and community/workplace interventions could reduce risk of food insecurity and improve the health of workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 66 publications
1
53
1
1
Order By: Relevance
“…Em pesquisa realizada com imigrantes fazendeiros que viviam nos Estados Unidos, foi demonstrado que os que estavam em IA em geral, apresentavam maior idade, gastavam 30% de sua renda com comida, e tinham sobrepeso 43 . Velásquez-Melendez et al 44 explicaram que quando comparadas as mulheres obesas, entre os diferentes níveis de IA (alcançados pela Escala Brasileira de Insegurança Alimentar), a IA moderada e leve apresentaram mais associação com a obesidade (OR=1,53; IC95%=1,22-1,93 e OR=1,22; IC95%=1,04-1,44, respectivamente).…”
Section: Definições Micro Ambientaisunclassified
“…Em pesquisa realizada com imigrantes fazendeiros que viviam nos Estados Unidos, foi demonstrado que os que estavam em IA em geral, apresentavam maior idade, gastavam 30% de sua renda com comida, e tinham sobrepeso 43 . Velásquez-Melendez et al 44 explicaram que quando comparadas as mulheres obesas, entre os diferentes níveis de IA (alcançados pela Escala Brasileira de Insegurança Alimentar), a IA moderada e leve apresentaram mais associação com a obesidade (OR=1,53; IC95%=1,22-1,93 e OR=1,22; IC95%=1,04-1,44, respectivamente).…”
Section: Definições Micro Ambientaisunclassified
“…Early estimates from a California-based sample of preschool-aged children, most of whom lived in farmworker families, reported that 37% of children were overweight or obese [10]. Subsequent studies of youth aged 2 years and older in Latino farmworker families have reported combined overweight/obesity rates of 47% [11] 49% [12] and 76% [13]. …”
mentioning
confidence: 99%
“…Consistent with this supposition, available evidence suggests elevated rates of overweight and obesity. 5,1214 …”
mentioning
confidence: 99%